2016
DOI: 10.1016/j.gfs.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural interventions for improved nutrition: A review of livelihood and environmental dimensions

Abstract: A diverse group of agricultural interventions aim to improve the nutritional status of women and children. These interventions range from the cultivation of bio-fortified crop varieties to home gardening to livestock intensification. We systematically review 42 evaluations of agricultural interventions for improved maternal and child nutrition. Using these evaluations, we identify three intervention typologies-Enhancement, Diversification, and Substitution-that reflect the differential impact of interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 69 publications
0
44
0
Order By: Relevance
“…In the most recent review, Fiorella et al (2016) examined 42 evaluations of agricultural interventions and their impact on child and maternal nutrition, and found that further information regarding agricultural programs' impact on time burdens, income, and expenditures would be useful in evaluation findings. They called for greater consideration of political, economic, environmental, and cultural factors in the assessment of particular projects (such as land tenure, weather patterns, resource access, and government policies), as these can substantially impact their outcome …”
Section: Agriculture and Nutritionmentioning
confidence: 99%
“…In the most recent review, Fiorella et al (2016) examined 42 evaluations of agricultural interventions and their impact on child and maternal nutrition, and found that further information regarding agricultural programs' impact on time burdens, income, and expenditures would be useful in evaluation findings. They called for greater consideration of political, economic, environmental, and cultural factors in the assessment of particular projects (such as land tenure, weather patterns, resource access, and government policies), as these can substantially impact their outcome …”
Section: Agriculture and Nutritionmentioning
confidence: 99%
“…A number of reviews of evidence on the impacts and pathways of impacts of nutritionsensitive agricultural programs on nutrition have been published in the past two decades (see, for example, Ruel, 2001;Berti et al, 2004;Randolph et al, 2007;Masset et al, 2012;Webb-Girard et al, 2012;Ruel and Alderman, 2013;Webb and Kennedy, 2014;Fiorella et al, 2016;Pandey et al, 2016;Ruel et al, 2018). Most reviews up to 2016 included variations of the same sets of empirical studies dating from as Box 9.1.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…The seeds of pulses such as the field pea (Pisum sativum), sweet lupin (Lupinus angustifolius), and lentil (Lens culinaris) are deemed to be good sources of dietary essential minerals (Curran, 2012;Vaz Patto et al, 2015), as summarized in Table 1. Their routine consumption in diverse cultures, amalgamated with an affordable and nontoxic nature constitutes a sustainable approach to alleviate mineral deficiencies through household consumption (Fiorella, Chen, Milner, & Fernald, 2016). Although mineral bioavailability in pulses are generally considered to be low due to the presence of antinutritional compounds (namely phytic acid and polyphenols) that form insoluble complexes during digestion (Alegría-Torán, Barberá-Sáez, & Cilla-Tatay, 2015), the chemical composition of pulses can differ greatly with genetic disposition (species and cultivars), growth environment, and soil conditions (Wang & Daun, 2006).…”
Section: Introductionmentioning
confidence: 99%